NKG2D-CAR memory T cells target pediatric T-cell acute lymphoblastic leukemia in vitro and in vivo but fail to eliminate leukemia initiating cells - Ibáñez-Navarro, Marta; Fernández, Adrián; Escudero, Adela; Esteso, Gloria; Campos-Silva, Carmen; Navarro-Aguadero, Miguel Ángel; Leivas, Alejandra; Caracuel, Beatriz Ruz; Rodríguez-Antolín, Carlos; Ortiz, Alejandra; Navarro-Zapata, Alfonso; Mestre-Durán, Carmen; et al. (Frontiers in Immunology, 2023)
Refractory/relapsed pediatric acute leukemia are still clinically challenging and new therapeutic strategies are needed. Interactions between Natural Killer Group 2D (NKG2D) receptor, expressed in cytotoxic immune cells, and its ligands (NKG2DL), which are upregulated in leukemic blasts, are important for anti-leukemia immunosurveillance. Nevertheless, leukemia cells may develop immunoescape strategies as NKG2DL shedding and/or downregulation. In this report, we analyzed the anti-leukemia activity of NKG2D chimeric antigen receptor (CAR) redirected memory (CD45RA-) T cells in vitro and in a murine model of T-cell acute lymphoblastic leukemia (T-ALL). We also explored how soluble NKG2DL (sNKG2DL) affected NKG2D-CAR T cells’ cytotoxicity and the impact of NKG2D-CAR T cells on Jurkat cells. In vitro, we found NKG2D-CAR T cells targeted leukemia cells and showed resistance to the immunosuppressive effects exerted by sNKG2DL. In vivo, NKG2D-CAR T cells controlled T cell leukemia burden and increased survival of the treated mice but failed to cure the animals. After CAR T cell treatment, Jurkat cells upregulated genes related to proliferation, survival and stemness, and in vivo, they exhibited functional properties of leukemia initiating cells. The data here presented suggest, that, in combination with other therapeutic approaches, NKG2D-CAR T cells could be a novel treatment for pediatric T-ALL.